Experimental Design of Biogas Production with Chicken and Cow Feces - albar albar; trisita novianti; ika deefi anna (Universitas Trunojoyo Madura, 2016)
Biogas production is carried out by utilizing livestock waste collected from the Sumenep dungkek area of Madura Island. Research was conducted in the area of power because the majority of the people live their daily lives by farming and raising cattle and chickens. The number of livestock in the dungkek area is more than 100 cows and 3000 chickens. However, almost all waste generated from livestock is only used as compost for agricultural land. Meanwhile, rural communities in their own way still use traditional methods, namely firewood and kerosene for cooking activities. Furthermore, the study will calculate the exact composition of a mixture of chicken and cow manure used in making biogas. The exact composition of chicken and cow manure is 50% chicken and 50% cow manure were in this study using 1.5 kg cow and 1.5 kg chicken manure. As in replication 1 and treatment 2 where biogas volume value 4.71 cm3 and methane gas 3.938 were obtained, which is the highest value obtained from all experiments. This shows that biogas from chicken manure is better than cow manure, but the amount of cow manure is more than chicken manure, so a combination of chicken and cow manure for biogas is used in this study. This study uses a completely randomized design (CRD) method with 2 factors, cow dung and chicken dung. Results of the composition of the mixture of selected cow and chicken dung to produce biogas will be the basis for making biogas reactors for home units